THE EFFECTIVENESS OF INTERACTIVE DIGITAL QUIZZES IN IMPROVING STUDENTS' UNDERSTANDING OF ISLAMIC JURISPRUDENCE LEARNING - Abd Gani; Atnawi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study was motivated by the low level of students' understanding in Islamic Jurisprudence (Fiqh) learning, as reflected in limited classroom participation, low enthusiasm in responding to teachers' questions, and difficulties in comprehending learning materials. These challenges highlight the need for innovative instructional strategies capable of creating a more engaging, interactive, and student-centered learning environment through the integration of interactive digital quizzes. This study aims to describe the implementation of interactive digital quizzes as an instructional innovation in Fiqh learning to enhance students' understanding and to identify the supporting and inhibiting factors influencing their implementation at Mauidzul Amin Islamic Junior High School, Pamekasan, Indonesia. A qualitative approach with a case study design was employed. Data were collected through classroom observations, semi-structured interviews, and documentation involving the school principal, Fiqh teacher, and students. The collected data were analyzed using data reduction, data display, and conclusion drawing, while data credibility was ensured through source and technique triangulation. The findings indicate that interactive digital quizzes improved students' classroom participation, learning enthusiasm, and conceptual understanding of Fiqh. Supporting factors included students' learning motivation, teachers' pedagogical competence, and adequate digital facilities. However, implementation was constrained by unstable internet connectivity, limited digital devices, and varying levels of students' digital literacy. Overall, interactive digital quizzes represent an effective innovation for improving Fiqh learning outcomes.